PEMBERDAYAAN PETANI MELALUI PENGETAHUAN PENETAPAN HARGA JUAL DALAM MEMPERKUAT MANAJEMEN PEMASARAN DI KELOMPOK TERNAK SAPI POTONG LEMBU MEKAR DI KECAMATAN BOLIOHUTO - Sri Yenny Pateda (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service aims to increase farmer knowledge about the importance of setting selling prices, especially in the marketing management of beef cattle which are managed independently by beef cattle farmers. Pricing plays a role as a determining variable in revenue for farmers who make beef cattle as a source of income. This community service activity is carried out using the counseling method, in the form of an explanation of the importance of setting a selling price, pricing methods in supporting effective marketing and the factors that influence selling prices. Community service activities using the extension method are able to increase farmers' knowledge of the importance of the selling price of beef cattle, so that it will affect the marketing management of beef cattle to be sold by breeders. The members of the farmer group were able to re-describe effective marketing through the determination of the selling price and the method of determining the selling price as well as the factors that influence the selling price of beef cattle.